STUDY OFF FISHING NELAYAN KELURAHAN BAGAN HULU KECAMATAN BANGKO KABUPATEN ROKAN HILIR PROVINSI RIAU - Lamun Bathara; Eni Yulinda; Hannum Gusliani (Berkala Perikanan Terubuk, 2012)
The research was implemented in Bagan Hulu Village, Bangko District, RokanHilir Regency, Riau Province at February 2012. The purpose of this research is todescribes fisher’s business beside catching fish and determine the income fromthat business. The methods that used in this research is survey method, thetechnique sample that applied is simple random sampling. Fisher population thathas been working beside catching fish is about 101 peoples. It is about 30% fromthis population are taken as respondent.The fisher jobs beside catching fish in this district is Bakau wood seller about 46,7%; BBM merchant is about 13,3%; oil palm farmer is about 13,3%; sand carrier isabout 16,7%; motorcycles travel rent is about 6,7%; and work at fisheries sourcesprocess is about 3,3%. The income for the fisher, from the business besidecatching fish is about Rp.250.000 – Rp.850.000 per month.Keywords: Fisher, Off Fishing, Income.